2015
DOI: 10.1111/obr.12261
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐component molecular‐level body composition reference methods: evolving concepts and future directions

Abstract: Excess adiposity is the main phenotypic feature that defines human obesity and that plays a pathophysiological role in most chronic diseases. Measuring the amount of fat mass present is thus a central aspect of studying obesity at the individual and population levels. Nevertheless, a consensus is lacking among investigators on a single accepted “reference” approach for quantifying fat mass in vivo. While the research community generally relies on the multicomponent body-volume class of “reference” models for q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 70 publications
0
90
0
6
Order By: Relevance
“…The specific gravity of fat is 0.900 g/cm 3 and the specific gravity of lean body mass is 1.095/cm 3 . 10,11 This means that fat is weight less per 1 cm 3 , but volume is larger. It has been reported that the fat mass of the thigh muscle in sarcopenia is increased compared to non sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The specific gravity of fat is 0.900 g/cm 3 and the specific gravity of lean body mass is 1.095/cm 3 . 10,11 This means that fat is weight less per 1 cm 3 , but volume is larger. It has been reported that the fat mass of the thigh muscle in sarcopenia is increased compared to non sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent technological advances highlight the opportunities to expand model applications to new subject groups and measure components such as total body protein [11].…”
Section: Multi-compartment Models (Four or More Compartments) Modelsmentioning
confidence: 99%
“…He conceived of the human body as two components, fat and "lean body mass", each with an assumed stable density of 0.900 g/cm 3 and 1.095 g/cm 3 , respectively [10][11][12].…”
Section: Two-component Modelmentioning
confidence: 99%
“…Međutim, danas druge tehnike procene telesne kompozicije, kao što su određivanje ukupnog telesnog kalijuma (TBK), ukupne telesne vode (TBW), DXA i magnetna rezonanca zauzimaju vodeće mesto u proceni telesnog sastava. Takođe postoje i multikomponentni hemijski metodi koji uključuju više od jedne metode procene i korisni su za aplikaciju u primenjenim istraživanjima [7]. …”
unclassified